PERKARA PERCERAIAN YANG DIPUTUS DENGAN VERSTEK - Sanyoto Sanyoto (Faculty of Law, Universitas Jenderal Soedirman, 2009)
The court changed the divorce of a model and also an announcer Andhara Early to her husband Chesa in the Islamic Court of south Jakarta. This divorce was granted by the justice of the supreme court. This case is very interesting because the accused whom his place has been known and has been called three times properly kept his mind not to attend on the court session. Although has been called properly according to the article 125 HIR/149 RBg the absent of the accused on the court session gave the authority to the judge decided his thought vertically.His thought of the decision was depended on the accusation which is proposed on the court session and was supported by the rational argumentation of accusation. The Authentication from the plaintif ascertained the judge that the rational argumentation could be proved, with the result that the judge granted the accusation of divorce.This cose showed that the process of the court meeting by the absent of the accused made the divorce went fast. Kata Kunci : cerai, Verstek